2019
DOI: 10.32607/20758251-2019-11-2-17-27
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Biomarkers of Brain and Spinal Cord Astrocytomas

Abstract: Spinal cord astrocytomas are rare diseases of the central nervous system. The localization of these tumors and their infiltrative growth complicate their surgical resection, increase the risk of postoperative complications, and require more careful use of radio- and chemotherapy. The information on the genetic mutations associated with the onset and development of astrocytomas provides a more accurate neoplasm diagnosis and classification. In some cases, it also allows one to determine the optimal methods for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 99 publications
(135 reference statements)
0
8
1
Order By: Relevance
“…According to the reviewed literature, p53 positivity is common in DMGSCs (20-50%) 5,16 and WHO III-IV spinal cord astrocytomas (60-67%). 32 The co-occurrence of the H3 K27M and TP53 mutations in gliomas had a trend of poorer prognosis (13.5 ± 2.3 months) compared to that of gliomas without TP53 mutation (20.0 ± 3.85 months) but had no significant effect on survival period. Some authors postulate that the H3 K27M mutation is a key driver mutation, and that the tumor suppressor gene product p53 positivity, indicative of a loss-of function mutation, plays an essential role in tumor development in both pediatric and adult spinal cord high-grade gliomas.…”
Section: Discussionmentioning
confidence: 91%
“…According to the reviewed literature, p53 positivity is common in DMGSCs (20-50%) 5,16 and WHO III-IV spinal cord astrocytomas (60-67%). 32 The co-occurrence of the H3 K27M and TP53 mutations in gliomas had a trend of poorer prognosis (13.5 ± 2.3 months) compared to that of gliomas without TP53 mutation (20.0 ± 3.85 months) but had no significant effect on survival period. Some authors postulate that the H3 K27M mutation is a key driver mutation, and that the tumor suppressor gene product p53 positivity, indicative of a loss-of function mutation, plays an essential role in tumor development in both pediatric and adult spinal cord high-grade gliomas.…”
Section: Discussionmentioning
confidence: 91%
“…Notably, in the described study, no specimen in the cohort displayed the BRAFV600E mutation. A very recent survey of the literature data reported that the main genetic variations associated with spinal cord astrocytomas involved BRAF-KIAA1549 fusions in about 32% of cases, and TP53 mutations in 60-67% of WHO grades III-IV spinal cord astrocytomas (27). Generally, it was also established that the molecular profile of astrocytomas in children differ significantly from the adult variants and mainly contain mutations in BRAF, H3F3A and ATRX genes.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, it was also established that the molecular profile of astrocytomas in children differ significantly from the adult variants and mainly contain mutations in BRAF, H3F3A and ATRX genes. However, to date, there is no information on the identification of specific spinal cord astrocytomas markers such IDH1/2, H3F3A and FGFR2 related to brain glial tumors (27).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphatase PTEN is involved in the dephosphorylation of membrane-bound phosphatidylserine PIP3 to PIP2, and thus regulates the PKB/AKT signaling pathway (22). In addition, PTEN is reported to play a main role in negatively regulating the PI3K/AKT pathway and inhibit PTEN-regulated apoptosis (23).…”
Section: Introductionmentioning
confidence: 99%